2008
DOI: 10.1002/anie.200801870
|View full text |Cite
|
Sign up to set email alerts
|

Dendronized Polymer Organogels from Click Chemistry: A Remarkable Gelation Property Owing to Synergistic Functional‐Group Binding and Dendritic Size Effects

Abstract: The use of 1,3-dipolar cycloaddition reactions between azides and alkynes (click chemistry) has been extremely successful as a versatile synthetic tool to construct novel polymeric systems.[1] Whereas the main thrust has been focused on building up highly elaborate polymeric architectures, such as block copolymers, star polymers, dendrimers, and hyperbranched polymers, it is also noted that the physical properties of such poly(triazole)-based materials are little studied.[1c]Additionally, although there are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…Similar to 1-G1, the poor solubility properties of 2-G1 G1 in THF precluded its SEC examination. In addition to the expected polymer peak, the SEC chromatograms of all examined dendronized polymers also showed the presence of many low-molecular-weight (LMW) peaks, suggesting the formation of cyclic oligomers during the copolymerization process [9] (see Supporting Information for details). The calculated M w , PDI, degree of polymerization (DP) values, and weight percentage of LMW oligomers (up to [3+3]mer) are given in Table 1.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Similar to 1-G1, the poor solubility properties of 2-G1 G1 in THF precluded its SEC examination. In addition to the expected polymer peak, the SEC chromatograms of all examined dendronized polymers also showed the presence of many low-molecular-weight (LMW) peaks, suggesting the formation of cyclic oligomers during the copolymerization process [9] (see Supporting Information for details). The calculated M w , PDI, degree of polymerization (DP) values, and weight percentage of LMW oligomers (up to [3+3]mer) are given in Table 1.…”
Section: Resultsmentioning
confidence: 95%
“…Hence, sequential introduction of the azide or acetylene functionalities was used. The known monoacid monoesters 7-Gm [9] were first coupled to propargyl amine in the presence of 1-hydroxybenzotriazole (HOBt) and a coupling reagent to produce the propargyl amides 8-Gm in 80-92 % yield. It was found that EDCI was useful for preparation of the first-generation (G1) dendrimer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations